Comparison of the young aged and elderly female users' adoption of mHealth services. Issue 10 (31st October 2022) - Alam, Mohammad Zahedul; Khanam, Liza
Abstract: The authors' aim in this study was to investigate the factors influencing the adoption of mHealth services between the young aged and the elderly female in Bangladesh. Using the extended Technology Acceptance Model (TAM) with three additional latent variables, i.e., perceived reliability, price value and technology anxiety, the proposed model was empirically examined based on the required data from a total survey of 542 respondents. Researchers revealed that perceived usefulness had significant impact on behavioral intention for both the young aged and the elderly female but perceived ease of use was insignificant for both groups. Perceived reliability and price value were found to have strong impact on actual usage. But the effect of technology anxiety was significant for elderly female but insignificant for young-aged female due to age characteristics. Therefore, this study is the first initiative to compare the adoption factors between young aged and elderly female in Bangladesh.